2018
DOI: 10.15376/biores.13.3.6280-6299
|View full text |Cite
|
Sign up to set email alerts
|

Consumer preferences for wooden furniture in Croatia and Slovakia

Abstract: During the last decade, the Slovak and Croatian furniture industry markets have experienced changes that have made these markets more interesting for domestic and foreign investors. Furniture manufacturers and retailers are still trying to determine the best ways to adjust to customer demands, and understanding the furniture preferences of customers would provide beneficial information to the furniture industry. The purpose of this study, which was conducted in 2016, was to improve the knowledge regarding diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…This indicates that price is important when the consumer buys furniture. Similarly, Mohamed and Abdullah (2006), Lihra and Graf (2007), and Lihra et al (2012), Andac and Guzel (2017), and Kaputa et al (2018) reported that price was an important factor concerning consumers' intention to purchase certain furniture. In particular, 19.4% stated they preferred wood composite since they viewed the lack of resistance to water and moisture of wood as a negative characteristic.…”
Section: Findings Of Wooden Materials For Domestic Usementioning
confidence: 91%
See 1 more Smart Citation
“…This indicates that price is important when the consumer buys furniture. Similarly, Mohamed and Abdullah (2006), Lihra and Graf (2007), and Lihra et al (2012), Andac and Guzel (2017), and Kaputa et al (2018) reported that price was an important factor concerning consumers' intention to purchase certain furniture. In particular, 19.4% stated they preferred wood composite since they viewed the lack of resistance to water and moisture of wood as a negative characteristic.…”
Section: Findings Of Wooden Materials For Domestic Usementioning
confidence: 91%
“…In this context, wood knowledge and awareness of these consumers were measured and the details involved in the purchase and use process of consumers were examined. Kaputa et al (2018) studied the Slovakian and Croatian furniture market and compared customers' furniture demands and preferences in both countries. The preferences of the customers was found to vary with respect to properties of furniture, materials used, furniture style, when buying indoor and outdoor furniture.…”
Section: Introductionmentioning
confidence: 99%
“…Although there was no objection to presence of different materials in furniture, solid wood material was primarily preferred in both countries. In both countries, the price was primarily effective in the purchase decision and production quality, style, warranty, safety and color are other effective factors (Kaputa et al, 2018). In the research examining the attitudes of consumers in Germany towards light furniture and the use of light wood-based materials in furniture design, weight feature has not been found to have a primary effect on attracting customers' attention, unlike more relevant factors such as quality, price and design (Knauf, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Given the above, we find the revised NEP scale to be a suitable tool to measure the environmental worldview of the Slovak public, as it is a globally accepted method allowing us to compare our results with the results of other researchers. Environmental awareness is increasing throughout the general public in Slovakia, and people are opting for the use of materials with a less negative impact on the environment ( Paluš et al, 2012 ; Kaputa et al, 2018 ; Navrátilová et al, 2020 ; Musova et al, 2021 ), yet the NEP has not been used to identify public environmental attitudes in Slovakia. Nevertheless, whether people act based on this preference depends mostly on their attitude towards the environment and environmental problems, as their behavior is affected by their attitudes.…”
Section: Introductionmentioning
confidence: 99%